Bioética y virtualidad en la relación médico-paciente - Valenzuela P, Sergio (Revista Hospital Clínico Universidad de Chile, 2022)
The paper proposes, as the topic of analysis, the emergence of telemedicine, a tool that has been intensively used by doctors and other professionals during the covid pandemic. The essay, divided into two parts, first describes the current situation of telemedicine and afterwards proposes a few precautionary theses, related to telemedicine and the doctor-patient relationship according to the undestanding that the latter has been inherited and transmitted by medical anthropology and the medical humanities.